The relationship between energy subsidies, oil prices, and CO2 emissions in selected Asian countries: a panel threshold analysis - Dzul Hadzwan, Husaini; Hooi Hooi, Lean; Rossazana, Ab. Rahim (Taylor and Francis Group, 2021)
Strategies to balance output growth and global warming are an important matter of discussion in the current environmental management literature. A decrease in energy prices encourages energy consumption. As energy subsidies and oil prices are a major influence on the overall energy price, they also influence the level of CO2 emissions associated with output growth. In this article, we investigate the asymmetric impact of energy subsidies, oil prices, and economic output on CO2 emissions. We used a panel dataset of 20 selected oil producing countries in Asia from 2010 to 2018. We employed threshold analysis to acquire further knowledge concerning the asymmetric impact of energy subsidies, oil prices, and output on CO2 emissions. Our findings suggest that while an energy subsidy was significant in terms of resultant CO2 emissions, energy subsidies had a greater impact on CO2 emissions when the oil price is low. However, energy subsidies are not expected to cause significantly higher CO2 emissions when the value of the subsidy is at a low level. Third, these relationships follow the pattern consistent with the environmental Kuznets curve hypothesis only when the energy subsidy is relatively high. We consider an energy subsidy rationalisation program could serve to meet environmental management goals in energy use.